Immune reconstitution after transplantation of autologous peripheral stem cells in children: a comparison between CD34+ selected and nonmanipulated grafts - Flaadt, Tim; Jaki, Christina; Maier, Claus-Philipp; Amorelli, Germano; Klingebiel, Thomas; Schlegel, Paul Gerhardt; Eyrich, Matthias; Greil, Johann; Schulte, Johannes H.; Bader, Peter; Handgretinger, Rupert; Lang, Peter (Cytotherapy, 2024)
Background and aims - High-dose chemotherapy (HDC) followed by autologous stem cell transplantation (ASCT) improves the prognosis in pediatric patients with several solid tumors and lymphomas. Little is known about the reconstitution of the immune system after ASCT and the influence of CD34+ cell selection on the reconstitution in pediatric patients. - Methods - Between 1990 and 2001, 94 pediatric patients with solid tumors and lymphomas received autologous CD34+ selected or unmanipulated peripheral stem cells after HDC. CD34+ selection was carried out with magnetic microbeads. The absolute numbers of T cells, B cells and natural killer (NK) cells were measured and compared in both groups at various time points post-transplant. - Results - Recovery of T cells was significantly faster in the unmanipulated group at day 30, with no significant difference later on. Reconstitution of B and NK cells was similar in both groups without significant differences at any time. The CD34+-selected group was divided into patients receiving less or more than 5.385 × 106/kg CD34+ cells. Patients in the CD34+ high-dose group displayed significantly faster reconstitutions of neutrophiles and lymphocyte subsets than the CD34+ low-dose group. - Conclusions - Engraftment and reconstitution of leukocytes, B cells and NK cells after transplantation of CD34+ selected stem cells were comparable to that in patients receiving unmanipulated grafts. T-cell recovery was faster in the unmanipulated group only within the first month. However, this delay could be compensated by transplantation of >5.385 × 106 CD34+ cells/kg. Especially for patients receiving immunotherapy after HDC large numbers of immune effector cells such as NK and T cells are necessary to mediate antibody-dependent cellular cytotoxicity. Therefore, in patients receiving autologous CD34+-selected grafts, our data emphasize the need to administer high stem cell counts.